2019
DOI: 10.12659/msm.912545
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticles Dispersed in Phytochemical Exert Anti-Inflammatory Activity by Modulating Catalase, GPx1, and COX-2 Gene Expression in a Rheumatoid Arthritis Rat Model

Abstract: BackgroundLiterature shows that serum selenium concentration is low in rheumatoid arthritis (RA) patients. Biochemical properties of nanoparticles (NPs) are depend in its medium dispersed. Biochemical properties could effectively alter the therapeutic potential of NPs. Phytochemicals could serve as suitable medium for dispersion of NPs. P-Coumaric acid (CA) known to have anti-inflammatory activity.Material/MethodsIn the present experiment, we investigated the anti-inflammatory effect of SeNPs dispersed in 1% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 52 publications
(60 reference statements)
7
34
0
Order By: Relevance
“…We [25] also observed that SeNPs treated animals shows reduced anti-in ammatory molecules like, TNFα, IL-6 etc., To get insight in the mechanism of action of SeNPs in RA condition, in the present study we have analyzed the effect of SeNPs on activated neutrophils with reference to NETs. Freund's complete and incomplete adjuvants, p-coumaric acid, (CA) and Cell Death Detection ELISAPLUS (Version 14, Roche Diagnostics) were obtained from Sigma chemicals.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…We [25] also observed that SeNPs treated animals shows reduced anti-in ammatory molecules like, TNFα, IL-6 etc., To get insight in the mechanism of action of SeNPs in RA condition, in the present study we have analyzed the effect of SeNPs on activated neutrophils with reference to NETs. Freund's complete and incomplete adjuvants, p-coumaric acid, (CA) and Cell Death Detection ELISAPLUS (Version 14, Roche Diagnostics) were obtained from Sigma chemicals.…”
Section: Introductionsupporting
confidence: 56%
“…Se concentration is found to be low in serum of RA patients, indicating the essential role of Se in RA patients management [24]. Recently we observed that SeNPs dispersed in bio-active compound have excellent anti-arthritic activity in animal model [25].…”
Section: Introductionmentioning
confidence: 98%
“…In some cases, animals treated with SeNPs showed significant restoration of these enzyme levels compared to those treated with prednisolone (10 mg/kg/day) [ 63 ]. Three years later, this result was replicated by another research group, where an increase in the expression of antioxidant enzymes was also shown (GPx1 and catalase) [ 64 ]. In another study, the design of polypeptide composite SeNPs (0.5 mg/kg −1 , ‘Se@RuNPs’) showed anti-inflammatory effects.…”
Section: Nutritional Selenium Status In Rheumatoid Arthritismentioning
confidence: 67%
“…Recently, some preclinical studies with Se nanoparticles (SeNPs) have been carried out with the aim of proposing complementary therapies in RA. These studies have been conducted on the basis that the dosage and chemical form of Se is important, since it has been shown that high doses of Se compounds (organic and inorganic) or Se enriched yeast can cause toxicity [ 63 , 64 , 65 ]. Furthermore, it has previously been shown that ROS production is involved in RA pathogenesis by inducing an oxidative state that activates the inflammatory processes of the joints causing tissue damage in RA patients [ 66 ].…”
Section: Nutritional Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…The expression level of inflammatory cytokines (COX‐2, TNF‐α, IL‐1β, IL‐6, and MCP‐1) reverted back to near normal levels after supplying 500 µg kg −1 body weight (b.w.) SeNPs 107…”
Section: Nanotherapeutics Of Ra Based On Nanodrugsmentioning
confidence: 99%